The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/9842605
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell Sarcoma: A Case Report Demonstrating Morphological and Immunophenotypical Variability within a Single Lesion

Abstract: Langerhans cells are antigen presenting dendritic cells and tumours arising from these are rare. The tumours arising from these dendritic cells are divided into two categories according to a WHO classification: Langerhans cell histiocytosis and Langerhans cell sarcoma. It is the degree of atypia and clinical aggressiveness that distinguishes the two subtypes. Langerhans cell sarcoma (LCS) is a neoplastic proliferation of Langerhans cells which can occur in skin, bone marrow, lymph nodes, spleen, liver, and lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Based on histopathology and clinical aggressiveness, Langerhans cell tumors can be divided into two main groups: LCH, a cytologically benign proliferation, and LCS, a cytologically malignant proliferation 55 . Both groups preserve the phenotypic and ultrastructural features of Langerhans cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on histopathology and clinical aggressiveness, Langerhans cell tumors can be divided into two main groups: LCH, a cytologically benign proliferation, and LCS, a cytologically malignant proliferation 55 . Both groups preserve the phenotypic and ultrastructural features of Langerhans cells.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of primary Langerhans cell sarcoma is difficult, and it is necessary to differentiate it from other malignancies of the skin, including anaplastic large cell lymphoma, 4 malignant melanoma, 5 metastatic cancer, myeloid sarcoma, and malignant fibrous histiocytoma 6 . Langerhans cell sarcoma occurs at any age and involves many organs or tissues, including bone marrow, 7 lung, 8 lymph nodes, 9 liver, 10 skin, 11–13 and subcutaneous tissue 14 . Our case indicated that the differential diagnosis of Langerhans cell sarcoma should be borne in mind for cases with high FDG uptake of skin mass.…”
mentioning
confidence: 99%